Pentacoordinated Al3+‐Stabilized Active Pd Structures on Al2O3‐Coated Palladium Catalysts for Methane Combustion. Issue 35 (24th July 2019) - Duan, Huimei; You, Rui; Xu, Shutao; Li, Zhaorui; Qian, Kun; Cao, Tian; Huang, Weixin; Bao, Xinhe
Abstract: Supported Pd catalysts are active in catalyzing the highly exothermic methane combustion reaction but tend to be deactivated owing to local hyperthermal environments. Herein we report an effective approach to stabilize Pd/SiO2 catalysts with porous Al2 O3 overlayers coated by atomic layer deposition (ALD). 27 Al magic angle spinning NMR analysis showed that Al2 O3 overlayers on Pd particles coated by the ALD method are rich in pentacoordinated Al 3+ sites capable of strongly interacting with adjacent surface PdO x phases on supported Pd particles. Consequently, Al2 O3 ‐decorated Pd/SiO2 catalysts exhibit active and stable PdO x and Pd–PdO x structures to efficiently catalyze methane combustion between 200 and 850 °C. These results reveal the unique structural characteristics of Al2 O3 overlayers on metal surfaces coated by the ALD method and provide a practical strategy to explore stable and efficient supported Pd catalysts for methane combustion. Abstract : Staying active : Al2 O3 overlayers on Pd particles coated by atomic layer disposition were rich in pentacoordinated Al 3+ sites capable of strongly interacting with adjacent surface PdO x phases on supported Pd particles. The resulting active and stable PdO x and Pd–PdO x structures catalyzed methane combustion efficiently between 200 and 850 °C (see picture; o‐Pd/SiO2 ‐T denotes the supported catalyst comprising Pd octahedra on SiO2 nanospheres).